Exploring the antimicrobial potential of lactobacilli against early-stage and mature biofilms of Staphylococcus aureus and Pseudomonas aeruginosa - Singh, Niharika; Gulhane, Rohini Devidas; Singh, Anamika; Goel, Maitri; Udelal, Pudke Payal; Sangwan, Vikas; Sihag, Manvesh Kumar; Goel, Gunjan; Panwar, Harsh; Puniya, Anil Kumar (Frontiers in Chemistry, 2025)
Bacterial biofilms are dynamic, complex and very adaptive, and can cause harm to health problems in both human and animals; besides posing a serious threat to industry. This study presents the potential of cell free preparations of lactobacilli isolated from breast milk (HM; n=11) and infant faecal (IF; n=15) samples to impact the growth of Staphylococcus aureus and Pseudomonas aeruginosa biofilms. The anti-biofilm activity of three distinct cell free preparations viz. un-treated cell free supernatant (CFS), pH neutralized CFS (N-CFS), and heat-treated CFS (H-CFS) was examined against both early stage and mature biofilms. While the post-incubation strategy examined the impact on mature biofilms, the co-incubation treatment assessed the impact of CFS on adhesion and initial colonization. When compared to post-incubation treatment (HM3; 67.12 %), the CFSs exhibited greater inhibitory activity during co-incubation (IF9; 85.19%). The un-treated CFS exhibited most promising biofilm inactivation; while the activity was not completely lost upon pH neutralization and heat treatment. After treating with H-CFSs and N-CFSs, the population of S. aureus and P. aeruginosa bacterial cells in the biofilm moderately decreased by 40-60%. Microscopic observations showed that after CFS challenge, the integrity of the biofilm conformation was destroyed. According to principal component analysis (significance level at p < 0.05), the most promising anti-biofilm activity against both test pathogens was found in the CFS of Lacticaseibacillus paracasei HM1.